1973
DOI: 10.1203/00006450-197308000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Relations between Placental Concentrations of Chorionic Somatomammotropin (Placental Lactogen) and Growth: A Study Using the Twin Method

Abstract: ExtractConcentrations of chorionic somatomammotropin (HCS) in extracts of homogenized placentas from 125 viable twin pairs were determined by radioimmunoassay. The intraclass (within-pair) correlation for placental concentration of HCS (C-HCS) was 0.64, and for total placental content of HCS (TPHCS) 0.59, both significant at P < 0.0,01. Individual differences within twin pairs were shown to be related to both fetal and postnatal growth. The co-twin method was used to assess these relations of HCS with growth v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1976
1976
1987
1987

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The latter authors do not think that hCS represents a true fetal equivalent of pituitary growth hormone, which is unessential for fetal growth (Blizzard and Alberts, 1956;Reid, 1960;Steiner and Boggs, 1965), but that it produces alterations in maternal metabolism which promote fetal growth indirectly. Our own studies in twins (MacMillan et al, 1973), which showed a strong positive relation between relative twin size and placental hCS concentration, raised the question whether hCS affects fetal growth other than via the maternal circulation.…”
mentioning
confidence: 90%
“…The latter authors do not think that hCS represents a true fetal equivalent of pituitary growth hormone, which is unessential for fetal growth (Blizzard and Alberts, 1956;Reid, 1960;Steiner and Boggs, 1965), but that it produces alterations in maternal metabolism which promote fetal growth indirectly. Our own studies in twins (MacMillan et al, 1973), which showed a strong positive relation between relative twin size and placental hCS concentration, raised the question whether hCS affects fetal growth other than via the maternal circulation.…”
mentioning
confidence: 90%